2016
DOI: 10.1021/acs.macromol.6b00165
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguring Nanocomposite Liquid Crystal Polymer Films with Visible Light

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…Another strategy to create LCE actuators capable of complex shape change without complex alignment is to spatially control the stimulus response of a film. Hauser et al showed that by doping a surface‐aligned LCE with gold nanoparticles, white light could heat the nanoparticles enough to give rise to local shape change in an LCE . Using a modified projector, light was localized to specific regions in the film to select the area of stimulus, causing localized out‐of‐plane shape changes.…”
Section: Applications Of Lcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy to create LCE actuators capable of complex shape change without complex alignment is to spatially control the stimulus response of a film. Hauser et al showed that by doping a surface‐aligned LCE with gold nanoparticles, white light could heat the nanoparticles enough to give rise to local shape change in an LCE . Using a modified projector, light was localized to specific regions in the film to select the area of stimulus, causing localized out‐of‐plane shape changes.…”
Section: Applications Of Lcesmentioning
confidence: 99%
“…bending and twisting, and Gaussian curvature become accessible with complex alignment. The potential of this control was first explored theoretically by Modes et al Following these predictions, several examples of densely‐crosslinked liquid crystal networks by Ware and White, Hauser et al, and others, with patterned director orientations were demonstrated . Surface alignment has emerged as the leading methodology for such complex alignment patterns, although it is possible to use both magnetic and mechanical alignment for certain patterns.…”
Section: Applications Of Lcesmentioning
confidence: 99%
“…For instance, by scanning the light as will, the capillary‐like moving, microwalker, helical rolling and swimming have been demonstrated . Applying structured light onto a uniform film, the spatially and temporally controlling of the shape morphing and biomimetic swimming and versatile locomotion were demonstrated with microscale LCN actuator . In another case, the structured light was utilized to propel fluid slug motion in microtubes of different shapes …”
Section: Light‐driven Self‐sustainable Motionmentioning
confidence: 99%
“…Recently, the use of azobenzenes with fast thermal cis‐to‐trans back‐relaxation in combination with the creation of a feedback loop based on self‐shadowing has created fast and self‐sustained motion of polymeric film and shows promising applications for transport and self‐cleaning surfaces. The motion is governed by a thermal effect and the photo‐responsive azo‐derivatives dyes can be replaced by any component able to quickly dissipate light into heat, for example, dyes or photo‐stabilizers, or inorganic particles . The heat dissipated from the photo‐excited dopants throughout the LCN induces anisotropic changes in the dimensions of the network by thermal deformation and a large bending of the film.…”
Section: Introductionmentioning
confidence: 99%